Healing family relationships eaudiobook A guide to peace and reconciliation. - Rienow, Rob (christianaudio, 2020)
Every family is hurting, and the wounds that come from our relatives can be deeper than all others. Conflict within a family can range from daily frictions and annoyances to rage and hatred and eventually estrangement. We want things to be different but have no idea where to start. After twenty-five years of ministering to families, Rob Rienow believes reconciliation is at the heart of the gospel-reconciliation with God and one another. You will come away with specific steps you can take in your relationships with your family members to pursue peace and healing in your homes. Each chapter includes key biblical examples as well as present-day stories of families who have experienced God's help and healing-including the author's own miraculous healing of his relationship with his father. Our families can bring out the best, as well as the worst, in all of us. May this book guide you in making your home and family a blessing in a broken world.